SMALL GROUP DISCUSION (SGD) LEARNING MODEL ON UNDERSTANDING THE CONCEPT OF THE NATURE OF LIGHT IN SD NEGERI 1 PUGUH - Sobirin, M.; Suryani, Ela (Universitas Trunojoyo Madura, 2022)
The purpose of this study was to improve the ability of students of SD Negeri 1 Pug uh in understanding the concept of class IV. This type of research is quantitative research using experimental research methods. The research subjects consisted of 48 fourth grade students of SD Negeri 1 Pug u h. data collection techniques through tests, observations and interviews. The results show that we will use the small group discussion method based on internships:1. The value of tcount ttable is 3.898 2009 and Sig. There is a difference in the average ability of students to understand concepts, it can be seen from the case where the score (both) is 0.001. If 0.05, H0 is rejected and Ha is accepted. 2. The small group discussion model can improve students' understanding of concepts represented by Fcount5040 with a significance of 0.035 Value for 0.05 and R2 = 0.182 = 18.2%. The conclusion of this study is a small group discussion model based on internships. There are differences between the use of the lab model and other models, which may affect your understanding of the concept of the nature of light.